2010
DOI: 10.1038/onc.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer ascites protects from TRAIL-induced cell death through αvβ5 integrin-mediated focal adhesion kinase and Akt activation

Abstract: Interactions between ovarian cancer cells and the surrounding tumor microenvironment are not well characterized. We have earlier shown that ovarian cancer ascites induces Akt activation and protect tumor cells from TRAIL-induced apoptosis. Here, we investigated the mechanism by which ascites activates Akt. The ability of ovarian cancer ascites to activate Akt and inhibit TRAILinduced cell death and caspase activity was decreased by heat inactivation, but was retained in ascites fractions 45 kDa. The survival p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 37 publications
11
91
0
1
Order By: Relevance
“…Unsurprisingly, given the heterogeneity of ascites, the magnitude of the efects varies depending on the cell line and ascites tested [74,75]. Multiple signaling pathways are activated by ascites in cancer cells, including up-regulation of anti-apoptotic protein Mcl-1 through ERK1/2-Elk-1 [76], up-regulation of anti-apoptotic protein c-FLIP [74], and activation of Akt through αvβ5/FAK signaling [75,77], all of which contributing to the pro-survival efect of ascites. Collectively, these data support the notion that ascites is a tumor environment enriched with pro-tumorigenic molecules.…”
Section: What Are the Efects Of Ascites On Tumor Cells?mentioning
confidence: 99%
“…Unsurprisingly, given the heterogeneity of ascites, the magnitude of the efects varies depending on the cell line and ascites tested [74,75]. Multiple signaling pathways are activated by ascites in cancer cells, including up-regulation of anti-apoptotic protein Mcl-1 through ERK1/2-Elk-1 [76], up-regulation of anti-apoptotic protein c-FLIP [74], and activation of Akt through αvβ5/FAK signaling [75,77], all of which contributing to the pro-survival efect of ascites. Collectively, these data support the notion that ascites is a tumor environment enriched with pro-tumorigenic molecules.…”
Section: What Are the Efects Of Ascites On Tumor Cells?mentioning
confidence: 99%
“…Reducing extracellular signals occur at several levels, through cell surface receptors (such as integrins, cadherins and IGF-IR [34][35][36][37]), through the signalling cascades emanating from those receptors (such as the PI3K/Akt and ERK signalling pathways) and through the signalling molecules connecting receptors to pathways (such as Src family kinases and FAK [38]). EMT has been linked to suppression of anoikis via depletion of E-cadherin and expression N-cadherin to protect cells against anoikis [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Blocking experiments demonstrated that the antiapoptotic actions of vitronectin were due to interactions with b 1 , b 3 , and b 5 , but not b 2 or b 4 integrins, confirming that the mechanism through which vitronectin enhances viability of neutrophils is by interaction with specific integrins, particularly those that include the b 1 , b 3 , or b 5 subunits, consistent with well described interactions between vitronectin and these integrin subunits ( The ability of vitronectin to diminish neutrophil apoptosis was not limited in these studies to spontaneous cell death, but also was present when apoptosis was induced through engagement of death receptors by TRAIL. The mechanism by which vitronectin diminishes the effects of TRAIL on neutrophil apoptosis may be through activation of Akt, which has been shown to inhibit TRAIL receptor-induced cell death (34,35).…”
Section: Discussionmentioning
confidence: 99%